Legality of Notary Deals Concerning Land Selling Not At Actual Price - Ponimin Ponimin (Sultan Agung Notary Law Review, 2021)
Notary as PPAT is a public official who is given the authority to make authentic deeds regarding certain legal actions regarding land rights or property rights over apartment units. The formulation of the research problem is: How as a result of the notarial deed regarding the sale and purchase of land that did not match the actual price in Kendari City? This research method uses a sociological juridical approach with research specifications using descriptive research specifications. Meanwhile, the method of collecting research data is through field studies and literature studies. The data obtained were analyzed qualitatively. Qualitative analysis is carried out by describing and describing the data and facts resulting from a field study with an interpretation, evaluation, and general knowledge. The conclusions of this study are: As a result, the notary deed regarding the sale and purchase of land does not match the actual price in Kendari City has an impact on the Notary because it is not suitable Article 17 letter i Act No. 30 of 2004 concerning the Position of Notary Public. Where the action in question can affect the honor and dignity of the position of a Notary who can be subject to sanctions in accordance with Article 85 of Act No. 30 of 2004. The legal consequence is that there is a violation of Article 16 paragraph (1) of Act No. 30 of 2004 concerning the Position of Notary which may cause administrative sanctions in accordance with Article 85 of Act No. 30 Of 2004 which include: a. verbal warning, b. written warning, c. temporary dismissal, d. honorific dismissal; or, e. dishonorable discharge.